Scientific Periodicals Circulation in Lithuania in the First Half of the 19th Century: the Case of Vilnius University - Pacevičius, Arvydas (Knygotyra, 2024)
This article examines the evolution and circulation of scientific periodicals within the academic community of Vilnius. The study aims to determine how periodicals from abroad reached Lithuania, how they were stored at Vilnius University, and how scientists utilized these information resources. It was found that the concept of scientific periodicals in the early 19th century began to emerge in bibliographic classification and librarians’ documentation, with their form and content being equated to popular science and/or the continuous works of scientific academies and societies. The distribution of scientific periodicals, especially those received from abroad, faced obstacles due to repressive censorship, which were attempted to be overcome using alternative channels (services of street book vendors). Despite the “clutches” on scientific information, the periodicals collection at Vilnius University Library grew significantly between 1803 and 1832, catering to the needs of the academic community. The thematic and content analysis of this collection from a heritage perspective would be the subject of another study.
Keywords: scientific periodicals; continuous publications; distribution; repressive censorship; Vilnius University; periodicals circulation